2006
DOI: 10.1016/j.aca.2005.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Chromatic characterisation of three consecutive vintages of Vitis vinifera red wine

Abstract: Both standard and CIELAB colour parameters have been evaluated for three consecutive vintages of Vitis vinifera (Tempranillo variety). A simple and straightforward relationship between CI and L* has been derived. Dilution effects on colour for samples under fermentation and for several commercial wines have been studied under pH controlled conditions. Disruptions of equilibria responsible for colour at the typical wavelengths upon addition of iron have been assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…On the other hand, TP analysis is cumbersome with a derivatization reaction that demands a careful timing of the spectroscopic measurements, while TA quantification is straightforward and individual anthocyanins measurements are more reproducible enabling the number of replicas to be low. It should be kept in mind that the Prussian blue method here utilized for TP analysis was chosen for it was found to be less interference prone than the Folin-Ciocalteu, Chromatic characterization of the three aforementioned vintages have been previously studied and reported (Esparza et al, 2006). It is now feasible to try and find whether definite relationships exist among those parameters and the organic fraction of the same wines here analyzed.…”
Section: Component Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, TP analysis is cumbersome with a derivatization reaction that demands a careful timing of the spectroscopic measurements, while TA quantification is straightforward and individual anthocyanins measurements are more reproducible enabling the number of replicas to be low. It should be kept in mind that the Prussian blue method here utilized for TP analysis was chosen for it was found to be less interference prone than the Folin-Ciocalteu, Chromatic characterization of the three aforementioned vintages have been previously studied and reported (Esparza et al, 2006). It is now feasible to try and find whether definite relationships exist among those parameters and the organic fraction of the same wines here analyzed.…”
Section: Component Analysismentioning
confidence: 99%
“…For statistical purposes, results presented in this paper are completed with those reported elsewhere (Esparza et al, 2004) for the precedent vintage (2002), in order to ascertain a better statistical significance. On the other part, this entire group of data is employed together with chromatic parameters exhaustively studied for these three vintages (Esparza et al, 2006), in order to check the influence of the former on the latter.…”
Section: 1-wine Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, complexation studies have been carried out involving copper and zinc with synthetic solutions of selected polyphenols (catechin, rutin and quercetin) as well as with wine samples, concluding that both metals chelate with the studied polyphenols . Esparza et al (2006) studied the disruptions of equilibria responsible for colour of samples undergoing vinification and on a few commercial red wines at the typical wavelength upon addition of Fe(III). They concluded that a small quantity of iron in wines produces an increment of blue colour and in a decrease of red colour.…”
Section: Speciation and Fractionation Studiesmentioning
confidence: 99%
“…The significance of this dependence points out that the contribution of complexes of Fe with polyphenols to the color of dark honeys could be quite high. By similarity to the formation of blue complexes of Fe with polyphenols in wine, 30 this effect, especially evident in dark honeys, could be related to the batochrome displacement to the blue region and an increase of the intensity of the red increment, however, a further elucidation is required. No such effect has been described so far.…”
Section: Rank Correlation Analysismentioning
confidence: 99%